"Paradigmatic change" with much continuity? EU's approach to values in external policies in the age of contestation. Issue 1 (1st January 2019) - Rabinovych, Maryna; Novakova, Zuzana
ABSTRACT: This contribution aims to compare and contrast the evolution of "EU shared values" debate in the EU's external policy over the period from 2015 to 2018. In this introductory comment, we look at how the "values vs interests" dilemma plays out in recent EU's strategic documents such as the European Global Strategy, as well as at the state of debate in mass media, academia and civil society. We ask: Is the EU's external action becoming more normatively oriented or more pragmatic in response to internal and external contestation? How are changes in responses communicated, and how does contestation affect and how does the EU reflect such communicative processes? The two subsequent contributions, dealing with trade policy and the European Neighbourhood Policy, provide a detailed analysis of the evolving role values play in these two external policies.